Terensko delo pri pouku fizike - Repnik, Robert (Fizika v šoli, 2020)
The paper presents the advantages and disadvantages of fieldwork, which is currently being implemented in schools to a lesser extent. The fieldwork in an outdoor classroom is presented in detail. The outdoor classroom should have the appropriate equipment if we want it to be used often. Based on the curricula of subjects that include natural science contents, the didactic equipment of the outdoor classroom is suggested. In addition, the organization of fieldwork lessons by working in groups is proposed.
Keywords: didaktična oprema; fizika; organizacija poučevanja; terensko delo; zunanja učilnica